1996
DOI: 10.1086/310400
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Temperature Structure in the Coma Cluster of Galaxies with [ITAL]ASCA[/ITAL]

Abstract: Significant temperature variation is found from ASCA observations of the hot intracluster medium in the Coma cluster of galaxies. The whole cluster out to 1Њ from the center was covered by 14 pointings. The temperature of the hot gas in the outside region is estimated by correcting for the stray-light effect from the bright center. The inferred temperature is lower than 4.5 keV in the west region and higher than 10 keV in the east, both offset by 40Ј (1.6 Mpc for H 0 ϭ 50 km s Ϫ1 Mpc Ϫ1) from the center. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 21 publications
7
64
0
Order By: Relevance
“…Radio (Thierbach et al 2003, and references therein) and X-ray measurements of ROSAT, ASCA and XMM-Newton (Briel et al 1992;Honda et al 1996;Briel et al 2001;Neumann et al 2003) confirmed this suspicion. The X-ray structure of the cluster detected by ROSAT and ASCA extends ∼1…”
Section: Excessmentioning
confidence: 91%
See 1 more Smart Citation
“…Radio (Thierbach et al 2003, and references therein) and X-ray measurements of ROSAT, ASCA and XMM-Newton (Briel et al 1992;Honda et al 1996;Briel et al 2001;Neumann et al 2003) confirmed this suspicion. The X-ray structure of the cluster detected by ROSAT and ASCA extends ∼1…”
Section: Excessmentioning
confidence: 91%
“…• off the cluster core to the south-west direction (Briel et al 1992;Honda et al 1996). This structure, seen in the X-ray brightness and temperature distributions, is explained by the merging process of NGC 4839 with the Coma cluster.…”
Section: Excessmentioning
confidence: 97%
“…10a, 11a, and 12). However, it is smaller than the model for a major merger (D1044 ergs s~1), although the Coma Cluster is known as a merging cluster (see, e.g., Briel, Henry, & 1992 ;Bo hringer Vikhlinin, Forman, & Jones 1997 ;Honda et al 1996 ;Watanabe et al 1999). The low luminosity suggests that the ratio of mass between the main cluster and the merger subcluster or subclusters is fairly high.…”
Section: Hard X-ray Emissionmentioning
confidence: 94%
“…Subsequent pointed observations with Rosat showed that Coma has irregular structure on different scales and was most probably formed by hierarchical clustering of several subunits, which are still visible in their X-ray emission (White et al 1993). Observations with ASCA, and also the pointed Rosat observation, showed evidence of temperature structure in Coma (Honda et al 1996;Briel & Henry 1998;Donnelly et al 1999;Watanabe et al 1999). The interpretation of the temperature structure favors the ongoing merging of the subgroup around NGC 4839 with the main cluster, a scenario which is still debated.…”
Section: Introductionmentioning
confidence: 92%